Association of Inflammatory Markers/Cytokines with Cardiovascular Risk Manifestation in Patients with Endometriosis - Uzma Rafi; Shaaf Ahmad; Syeda Shazia Bokhari; Muhammad Amir Iqbal; Amna Zia; Muhammad Amjad Khan; Nabila Roohi (Mediators of Inflammation)
This study is aimed at determining the association of inflammatory markers and proinflammatory cytokines with cardiovascular risk manifestation in women with endometriosis as compared to healthy controls. A total of 181 females of reproductive age with the absence of other inflammatory or autoimmune disorders and a lack of hormonal therapy for at least 6 months voluntarily participated in this investigation. Patients were 81 females, laparoscopically diagnosed with endometriosis, while the control group comprised 80 healthy females without any pelvic pathology. All subjects were 20-40 years of age. Exclusion criteria were diabetes, obesity, hypertension, metabolic diseases, cardiovascular, and renal disorders. C-reactive protein, fibrinogen, homocysteine, interleukin-17, and interleukin-33 were analyzed using commercially available ELISA kits. For statistical interpretation, the unpaired Student “t” test was used. All inflammatory markers and cytokines demonstrated elevated levels (P<0.001) in endometriosis patients as compared to healthy controls. The results of the study revealed that the patients with endometriosis demonstrate a hypercoagulable status due to inflammation, which initiates atherosclerosis and associated complications. Hence, endometriosis can cause a risk of cardiovascular disorders in these patients.